Digital Senegal for inclusive growth technological transformation for better and more jobs - Cruz, Marcio José Vargas da; Dutz, Mark Andrew 1951-; Rodríguez-Castelán, Carlos (World Bank, 2021)
Digital Senegal for Inclusive Growth explores possible solutions for a more intensive use of digital technologies, especially by small and medium enterprises, to increase their productivity and create more quality jobs. The report will contribute to helping women and young people in particular to gain access to decent work and therefore reduce their exposure to poverty. Appropriate use of this report will make it possible to succeed in the challenges of digital transformation, especially in the context of a relatively young population that is more open to innovation and change
Keywords: Digital Divide; Digital Economy; Digital Infrastructure; Employment; Inclusive Growth; Labor Skills Development; Technology Adoption